Investigation of Laboratory Experimental Methods for Determining the Acceleration Constant (g) and Comparison with Theoretical Values in Kabul
This research aims to identify the most accurate laboratory method for determining the acceleration due to gravity (g) at a specific location. Data were collected using four laboratory methods to measure g in the physics laboratory. The results from these methods were compared with theoretical values, and the most effective method was identified as the physical pendulum approach. The experimental value obtained for g in Kabul was gexp=978.767 cm/s2g_exp = 978.767 cm/s^2gexp​=978.767cm/s2, which differs by 0.3 from the theoretical value of gthe=978.4986 cm/s2g_the = 978.4986 cm/s^2gthe​=978.4986cm/s2. The experimental error was 0.3%, which is within the permissible range of laboratory instrument and calculation errors. , number=2, journal=Journal of Natural Sciences – Kabul University, author=Khawari, Rajab Ali, year=2022, month=Oct., pages=153–166